Development of the sensing platform for protein tyrosine kinase activity - Wei, Lan-Yi (MDPI, 2021)
A miniature tyrosinase-based electrochemical sensing platform for label-free detection of protein tyrosine kinase activity was developed in this study. The developed miniature sensing platform can detect the substrate peptides for tyrosine kinases, such as c-Src, Hck and Her2, in a low sample volume (1-2 mu L). The developed sensing platform exhibited a high reproducibility for repetitive measurement with an RSD (relative standard deviation) of 6.6%. The developed sensing platform can detect the Hck and Her2 in a linear range of 1-200 U/mL with the detection limit of 1 U/mL. The sensing platform was also effective in assessing the specificity and efficacies of the inhibitors for protein tyrosine kinases. This is demonstrated by the detection of significant inhibition of Hck (similar to 88.1%, but not Her2) by the Src inhibitor 1, an inhibitor for Src family kinases, as well as the significant inhibition of Her2 (similar to 91%, but not Hck) by CP-724714 through the platform. These results suggest the potential of the developed miniature sensing platform as an effective tool for detecting different protein tyrosine kinase activity and for accessing the inhibitory effect of various inhibitors to these kinases.